THE USE OF INDIGOFERA LEAF FLOUR (Indigofera sp.) AS A SUBSTITUTE OF SOYBEAN FLOUR IN THE GROWING FEED OF RED TILAPIA (Oreochromis sp.) - Norma Valensi Putri; Siti Hudaidah; Ediwarman Ediwarman; Novita Panigoro; Agus Setyawan (University of Lampung, 2022)
Feed is one of the most important aspects that cannot be left out in the fish farming process. One of the problems often faced by cultivators is the high price of feed due to the use of imported raw materials, such as soybean meal flour. To reduce the use of soybean meal flour, a new innovation was carried out in the form of substitution of local raw materials, namely Indigofera sp. This study aims to determine the effect of TDI (Indigofera sp.) as a substitute for soybean meal flour on growth performance on rearing red tilapia (Oreochromis sp.). This study used a completely randomized design with 4 treatments and 3 replications. P1 (without TDI usage), P2 (10% TDI usage), P3 (20% TDI usage), P4 (30% TDI usage). The data obtained were analyzed using analysis of variance (ANOVA) then further tested with Duncan's test. Based on statistical analysis, the test feed had a significant effect (p<0.1) on FCR was not significantly different (p>0.1) on the growth of absolute weight, absolute length, SGR, and SR of fish. The result of this study is that the use of TDI (Indigofera sp.) can be used up to a dose of 30% as a substitute for soybean meal flour in red tilapia feed, because it produces the same absolute weight growth, absolute length growth, SGR, and SR as the control feed.